An Analysis of Code Switching Used By Maudy Ayunda in the YouTube Video “Study Hacks Ala Maudy Ayunda” - Hutabarat, Novra Melisa P.; Lumban Tungkup, Miranda Kristin; Hutabarat, Esra Delima; Silitonga, Sarah Priscilla; Simanjuntak, Kesmi Veronika; Sianturi, Bella Sonia; Pardede, Dwi Angeli; Samosir, Deswita Fitriani; Malau, Sara Stefani (Journal of English Language and Education, 2025)
This study focuses on the phenomenon of code switching that appears in one of Maudy Ayunda's YouTube videos entitled "Study Hacks Ala Maudy Ayunda", with the aim of describing the types and the functions of code switching used by Maudy Ayunda on her YouTube channel, both of which are analyzed using Hoffman's theory. This study uses a qualitative method with content analysis based on Hoffmann's theory. Data is taken from the video script itself, and the results are calculated using the Sudijono formula. The results of the study after analyzing the video, the author found that there were sixty-five data in the types and functions of code switching. In the types of code switching, intra sentential and intra sentential code switching are the highest types, namely 31 data (47.6%) and tag sentential code switching is the lowest type, namely 3 data (4.6%). Meanwhile, in the code switching function, talking about particular topic is a function of code switching that has the highest data, which is 23 data (35.3%), then followed by intention of clarifying the speech content for interlocutor, which consists of 13 data (20%), then followed by being emphatic about something (express solidarity) and repetition, which is 10 data (15.38%), then followed by interjection and expressing group identity, which each have 4 data (6.15%) and the lowest is quoting somebody else, which is only 1 data (1.53%).